بارامترات تشغيل مرشح ثنائي الطبقة بنظام ترشيح فوق سريع - قصير أحمد; جناد هيثم; علي كاترين محمد (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف البحث إلى استخدام مرشح ثنائي الطبقة ( رمل الكوارتزي- الانتراسيت) بنظام الترشيح فوق السريع لتنقية المياه السطحية, وقد تمت دراسة فعالية هذا المرشح في إزالة عكارة المياه ضمن سلسلة كبيرة من التجارب على نموذج مخبري بعكارات 30,60 g/m3 وسرعات ترشيح30-45-60 m/h . تم في هذا البحث تحديد بعض بارامترات التشغيل التكنولوجية لعملية الترشيح، وهي سرعة الترشيح, فعالية التنقية, زمن الدورة الترشيحية, نظام الغسل (إعادة التنشيط). وبينت التجارب أنه بالإمكان استخدام الترشيح فوق السريع بحشوة ثنائية الطبقة بفاعلية جيدة من حيث مردود التنقية، وذلك من أجل سرعات ترشيح ضمن مجال 30-60 m/h, حيث تراوح مردود التنقية بين 90-97.8%. كما تمت عملية غسل الحشوة المرشحة باستخدام الهواء المضغوط والماء على مرحلتين, وباستخدام الماء النظيفة فقط, وتبين أن فعالية الغسل باستخدام الهواء المضغوط والماء على مرحلتين أكبر (98% وزمن قدره 8min). This research aims at using a dual media filter (quartzy sand-anthracite) by adopting the ultra-speed filtration system to purify surface waters. The efficiency of this method depends on the ability of removing turbid water by making many successive experiments on a laboratory sample with different turbidity and filtration speeds. The work involved the determination of some technical parametres concerning filtration such as infiltration speed, purification efficiency, duration of infiltration cycle and washing system.The results seem to indicate that it is possible to achieve good purification yield using this ultra-speed filtration with dual filling for filtration speeds from 30 to 60 m/h where the filtration yield varies between 90 97.8 %. Washing is done in only water- two stages using water and air, when it comes to washing efficiency it is clear that the best washing method is two stages using water and air (98% from 8 min).